"Na matança do boi a festa começa": experiências de criação cênica por meio dos saberes tradicionais na EEEP Joaquim Moreira de Sousa - Alencar, Shirley (2024)
This work has as its object of study the traditional knowledge of Boi do Ceará play, by Master Zé Pio, resident in Goiabeiras neighborhood in Fortaleza, with the aim of developing creative experience in arts at the public School of Professional Education (EEEP) Joaquim Moreira de Sousa, in Parangaba neighborhood. An artistic project was designed with a group of students from the 1st and 2nd years of professional technical courses from the perspective of ethnocenology aligned with art teaching. The project included three stages: the investigation of Boi Ceará party, where the participating students had the opportunity to learn about and understand the fundaments that guide the lark, based on a conversation with Master Zé Pio, in addition to expanding their ability to observe its elements: dance, characters, costumes, music and animals; experimentation and creation, when students were encouraged to explore expressiveness and collaboratively create their body narratives to create a presentation; and, finally, the socialization of the experiment to school. To develop the research, we used cartographic and ethnographic methods with participatory observation procedures, bibliographic review, field research and conversation circles recorded in audio recordings and photographs. The experience with Master Zé Pio showed that the knowledge of popular tradition is composed of elements incorporated by ancestry, becoming a fruitful territory for experimentation and learning, as well as the creative process in art created an environment of possibilities to compose expressive narratives of the body in interaction with space and with each other.